Microwave Assisted Synthesis of Some New Schiff's Bases - CHACKO, ELJO P.; RAO, GOPAL KRISHNA (Asian Journal of Chemistry, 2010)
In present work, the microwave irradiation induced, synthesis of N-(4-hydrazinocarbonyl phenyl)acetamide with different aryl aldehyde yields, N-[4-(substituted benzylidine)-hydrazino carbony phenyl]acetamide has been carried out.